Immune Response to Salmonella Enteritidis Infection in Broilers Immunized Orally With Chitosan-Based Salmonella Subunit Nanoparticle Vaccine - Han, Yi; Renu, Sankar; Patil, Veerupaxagouda; Schrock, Jennifer; Feliciano-Ruiz, Ninoshkaly; Selvaraj, Ramesh; Renukaradhya, Gourapura J. (Frontiers in Immunology, 2020)
Salmonella enterica serovar Enteritidis (S. Enteritidis, SE) infection in broilers causes a huge economic loss and public health risk. We previously demonstrated that orally delivered chitosan based (CS) Salmonella subunit nanoparticle (NP) vaccine containing immunogenic outer membrane proteins (OMP) and flagellin (FLA) of SE [CS-NP(OMP+FLA)] induces immune response in broilers. The objective of this study was to evaluate the dose- and age-dependent response and efficacy of CS-NP(OMP+FLA) vaccine in broilers. Three-day old birds were vaccinated and not booster or boosted once or twice. Additional groups were vaccinated at three weeks and boosted once later. Each dose of CS-NP vaccine had either 10 μg or 50 μg of OMP+FLA antigens. Our data revealed that two doses of vaccine were required to induce substantial immune response. Birds received 2 doses of CS-NP(OMP+FLA) vaccine at 3 days and 3 weeks of age with 10 μg antigens, and birds inoculated twice at 3 and 4 weeks of age with 50 μg antigens had lowest challenged bacterial load in the cecal contents with over 0.5 log10 reduction. In CS-NP(OMP+FLA) vaccinated birds, antigen-specific splenocyte proliferation, mucosal and systemic antibody responses and the frequency of IFNγ-producing T cells were increased compared to control groups. At the molecular level, in the cecal tonsils of CS-NP(OMP+FLA) immunized birds, mRNA levels of toll-like receptor (TLR) 2 and TLR 4, and cytokines IL-4 and IL-10 were upregulated suggesting the induction of both antibody and cell mediated immune responses. The CS-NP(OMP+FLA) vaccine given orally has the potential to induce a protective immune response against SE infection in broilers.